Pengaruh Latar Belakang Pendidikan, Pengalaman Kerja dan Keahlian Profesional Terhadap Efektivitas Sistem Pengendalian Intern di Lembaga Perkreditan Desa (LPD) Se-Kecamatan Kediri - Ni Made Winda Jatiningsih; Kadek Dewi Padnyawati; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2023)
One of the assets and income for traditional villages called by LPD so that it requires good management by the management. Adequate supervision needs to be owned by each LPD to prevent abuse of authority by various parties and financial practices that can lead to bankruptcy of the LPD. The population is LPD in Kediri by sample of 63 people. The research method used is quantitative. In order to predict education background, work experience, profesional skills toward dependent variable we used regression analysis. Based on the results, educational background, work experience and professional skills have a positive and significant effect on the internal control system. Based on the results of research on Village Credit Institutions in Kediri District, Tabanan Regency, it shows that educational background has a considerable influence. So that for the LPD in Kediri District in the future it is hoped that in selecting the chairman of the LPD and the supervisory body to consider a higher level of education.